2016
DOI: 10.1177/0001699316628614
|View full text |Cite
|
Sign up to set email alerts
|

Childhood residential mobility and long-term outcomes

Abstract: To study relations between childhood residential mobility and early adult outcomes, we use detailed longitudinal data on complete cohorts born in Norway between 1965 and 1980 (N ¼ 967 151) and information on all their relocations between municipalities. Results from models with and without sibling-fixed effects show that children with more residential moves are more likely to drop out of high school, to have a lower adult income and to experience early parenthood, although most of these associations are weak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 51 publications
(102 reference statements)
1
22
0
Order By: Relevance
“…Empirical evidence on the impact of childhood migration and residential mobility is diverse, with a literature emanating from different disciplinary perspectives that have examined a wide range of life outcomes, including school performance (Tucker et al 1998), school dropout (Astone and McLanahan 1994;Tønnessen et al 2013), mental health (Fowler et al 2014;Rumbold et al 2012;Tseliou et al 2016), social integration (Myers 1999a) and drug and alcohol use (DeWit 1998). While these studies broadly point to negative but weak associations between early migrations and life This article is protected by copyright.…”
Section: Impact Of Childhood Migration On Life Outcomes: a Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical evidence on the impact of childhood migration and residential mobility is diverse, with a literature emanating from different disciplinary perspectives that have examined a wide range of life outcomes, including school performance (Tucker et al 1998), school dropout (Astone and McLanahan 1994;Tønnessen et al 2013), mental health (Fowler et al 2014;Rumbold et al 2012;Tseliou et al 2016), social integration (Myers 1999a) and drug and alcohol use (DeWit 1998). While these studies broadly point to negative but weak associations between early migrations and life This article is protected by copyright.…”
Section: Impact Of Childhood Migration On Life Outcomes: a Reviewmentioning
confidence: 99%
“…A growing literature on child development has shown that migration and residential mobility can affect cognitive and behavioural development in childhood, with consequences on well-being later in life (Astone and McLanahan 1994;DeWit 1998;Fowler et al 2014;Myers 1999a;Rumbold et al 2012;Tønnessen, Telle and Syse 2013;Tseliou et al 2016;Tucker, Marx and Long 1998). However, it is unclear from this literature whether childhood relocations should enhance or detract mobility in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Higher levels of mobility have been linked to increased incidence of smoking ( Dong et al, 2005 ; Lee, 2007 ); increased alcohol onset and related problems ( DeWit, 1998 ); early initiation of drug use and drug-related problems ( DeWit, 1998 ; Gasper et al, 2010 ; Lee, 2007 ); and increased participation in anti-social behaviour ( Simpson and Fowler, 1994 ), deviance ( Haynie et al, 2006 ), violence ( Haynie and South, 2005 ), and more broad criminal activity ( Sharkey and Sampson, 2010 ). There are also gender specific sexual health impacts: females who move have been found to have increased rates of early and premarital sex and teenage pregnancy ( Dong et al, 2005 ; Stack, 1994 ; Tonnessen et al, 2013 ) and higher numbers of sexual partners ( Baumer and South, 2001 ) than females who remained residentially stable.…”
Section: The Inter-relation Between Mobility and Healthmentioning
confidence: 99%
“…Dramatic changes occur during adolescence, which may leave youth more susceptible to social, psychological, and biological factors that influence development, compared to other developmental stages (Kuh et al 2003). Therefore, the effects of residential mobility may be most harmful during adolescence (Tønnessen et al 2013; Pettit 2004; Fauth et al 2005). If residential mobility effects on education and delinquency are heterogeneous by age and/or gender, this may have important implications for targeting prevention efforts at the most vulnerable age and gender groups.…”
Section: Introductionmentioning
confidence: 99%